Native-Place Networks and Political Mobilization: The Case of Post-Handover Hong Kong. (September 2021) - Yuen, Samson
Native-place associations have played an indispensable role in the global migration of ethnic Chinese. Although there has been growing attention to their political role in advancing the Chinese state's interests, few studies have looked into how they are organized and how they operate vis-à-vis the state. This article focuses on post-handover Hong Kong, where native-place associations, despite their long presence, are still growing in number and sophistication after the 1997 handover. It posits that native-place associations there are forming a "cultural nexus" through which the Chinese state fosters political mobilization in support of its interests and policies. Based on an original set of event and biographical data, it shows that native-place associations are consolidating into a massive network connected by power-seeking elites. It also demonstrates how these associations seek to renew the significance of native-place and national identities. The findings point to how native-place associations may serve as a powerful cultural space for the Chinese state to project its influence offshore.